Copper decorated indium oxide rods for photocatalytic CO2 conversion under simulated sun light. (April 2022) - Wang, Xingdong; Ng, Derrick; Du, Haoran; Hornung, Christian H.; Polyzos, Anastasios; Seeber, Aaron; Li, Hexing; Huo, Yuning; Xie, Zongli
Abstract: In this work, copper (Cu) decorated indium oxide (In2 O3 ) rods were prepared via a simple wet chemistry method under mild temperature at atmospheric pressure. The resultant copper decorated indium oxide (Cu/In2 O3 ) composites showed changes in the morphology, composition, crystal property, oxidation status, optical property, and textural surface properties. The In2 O3 rods showed highly catalytic efficiency in reducing CO2 to CO, H2 and CH4 in the presence of water via a photocatalytic mechanism under simulated sun light. Incorporation of copper significantly increased the total conversion rates and regulated the selectivity. Total evolution rates of carbon-based products (CO and CH4 ) for Cu/In2 O3 with different Cu content were all greater than 1 mmol·gcat −1 ·h −1 . In addition to the high efficiency, copper addition also enhanced the selectivity towards forming carbon-based products (CH4 and CO), even amounting to 100% for 20% target copper addition. This low-cost preparation method, paired with high CO2 photoreduction efficiency and selectivity, has the potential for future industrial applications of these new Cu/In2 O3 composites. Graphical Abstract: Copper decorated In2 O3−x (OH)y rod-based superstructures were successfully prepared using a mild wet chemistry approach with high photocatalytic CO2 conversion activity and selectivity. The ease to scale up method is envisioned to be a potential leading candidate for CO2 gas remediation via renewable and green approach. ga1 Highlights: The copper (Cu) decorated indium oxide (In2 O3 ) rods were prepared via a simple wet chemistry method under mild conditions. In2 O3 rods were highly efficient for photocatalytic CO2 conversion in the presence of water under simulated sun light. The Cu decoration vitally altered physical and chemical properties of pristine In2 O3, specifically the optical property. The selectivity towards forming carbon-based products of CH4 and CO reached 100% with 20% Cu addition.